2020
DOI: 10.1136/annrheumdis-2020-217362
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from COVID-19 in a patient with spondyloarthritis treated with TNF-alpha inhibitor etanercept

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research. Patient consent for publication Obtained. Provenance and peer review Not commissioned; externally peer reviewed. This article is made freely available for use in accordance with BMJ's website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 6 publications
0
54
0
Order By: Relevance
“…Some patients with prior autoimmune and autoinflammatory conditions infected with SARS-CoV-2 have shown better outcomes may be due to baseline immunomodulatory medications. Some reports have shown that patients with ADs with prior treatment with hydroxychloroquine, TNFα antagonists [134], Anakinra [135], or Tocilizumab [136], may develop a mildest SARS-CoV-2 infection. These phenomena could be associated with a better control to COVID-19, and it may suggest that these medications, used chronically, decrease the severity of this infection.…”
Section: Cytokine Storm Syndrome (Css)mentioning
confidence: 99%
“…Some patients with prior autoimmune and autoinflammatory conditions infected with SARS-CoV-2 have shown better outcomes may be due to baseline immunomodulatory medications. Some reports have shown that patients with ADs with prior treatment with hydroxychloroquine, TNFα antagonists [134], Anakinra [135], or Tocilizumab [136], may develop a mildest SARS-CoV-2 infection. These phenomena could be associated with a better control to COVID-19, and it may suggest that these medications, used chronically, decrease the severity of this infection.…”
Section: Cytokine Storm Syndrome (Css)mentioning
confidence: 99%
“…18 . There are also a couple of case reports on anti-TNF- agents etanercept 19 and infliximab 20 therapy used successfully for COVID-19 patients with pre-existing auto-immune conditions. However, results of wider application of such therapy is still awaited.…”
Section: Introductionmentioning
confidence: 99%
“…4 In mice, TNFα blockade or the loss of TNFα receptor showed to reduce mortality or morbidity related to SARS-CoV2 infection. 5 Duret et al 6 reported a case of a patient treated with etanercept for spondyloarthropathy who rapidly recovered from COVID-19. Conti et al 7 described a case of a 67-year-old-psoriatic patient treated with adalimumab that did not develop any COVID-19 related symptom after several close contacts with COVID-19 confirmed cases.…”
mentioning
confidence: 99%